Investigating expectation effects using multiple physiological measures - Siller, Alexander; Ambach, Wolfgang; Vaitl, Dieter (Frontiers in Psychology, 2015)
The study aimed at experimentally investigating whether the human body can anticipate future events under improved methodological conditions. Previous studies have reported contradictory results for the phenomenon typically called presentiment. If the positive findings are accurate, they call into doubt our views about human perception, and if they are inaccurate, a plausible conventional explanation might be based on the experimental design of the previous studies, in which expectation due to item sequences was misinterpreted as presentiment. To address these points, we opted to collect several physiological variables, to test different randomization types and to manipulate subjective significance individually. For the latter, we combined a mock crime scenario, in which participants had to steal specific items, with a concealed information test (CIT), in which the participants had to conceal their knowledge when interrogated about items they had stolen or not stolen. We measured electrodermal activity, respiration, finger pulse, heart rate, and reaction times. The participants (n=154) were assigned randomly to four different groups. Items presented in the CIT were either drawn with replacement (full) or without replacement (pseudo) and were either presented category-wise (cat) or regardless of categories (nocat). To understand how these item sequences influence expectation and modulate physiological reactions, we compared the groups with respect to effect sizes for stolen vs. not stolen items. Group pseudo_cat yielded the highest effect sizes, and pseudo_nocat yielded the lowest. We could not find any evidence of presentiment but did find evidence of physiological correlates of expectation. Due to the design differing fundamentally from previous studies, these findings do not allow for conclusions on the question whether the expectation bias is being confounded with presentiment.